Holocellulose from a Winemaking By-Product to Develop a Biopolymeric System for Bacterial Immobilization: Adsorption of Ochratoxin A in Wine Model Solutions (Box–Behnken Design) - Verónica Carrasco-Sánchez; V. Felipe Laurie; Marcelo Muñoz-Vera; Ricardo Ignacio Castro (Toxins)
Significant agro-industrial waste is produced during the winemaking process, including grape stalks, which are a rich source of the valuable biopolymer holocellulose that can be utilized for biotechnological processes. The purpose of this study was to delignify grape stalks in order to extract holocellulose. Then Lactobacillus plantarum (LP) was immobilized in the interstitial spaces of holocellulose and then coated with natural polymers (chitosan, Ch; and alginate, Al) to create the Holo-LP/Ch/Al complex. A physicochemical analysis of the system revealed strong bacterial immobilization and stability. The efficiency of the complex in adsorbing ochratoxin A (OTA) from wine model solutions was assessed using a Box–Behnken design under various pH, time, and concentration conditions. The results showed that at pH 3.0, 75.39 min, and a complex concentration of 43.82 mg mL−1, the best OTA removal (53.68%) took place. Because of its physicochemical interactions, the complex showed improved OTA adsorption in acidic environments. This study demonstrates the potential of biopolymeric systems based on holocellulose for reducing mycotoxin contamination in beverages and stabilizing bacterial cells. These results offer a viable way to increase food safety and value winemaking by-products.